A Zebrafish Model for Chlamydia Infection with the Obligate Intracellular Pathogen Waddlia chondrophila - Fehr, Alexander G. J.; Ruetten, Maja; Seth-Smith, Helena M. B.; Nufer, Lisbeth; Voegtlin, Andrea; Lehner, Angelika; Greub, Gilbert; Crosier, Philip S.; Neuhauss, Stephan C. F.; Vaughan, Lloyd (Frontiers in Microbiology, 2016)
Obligate intracellular chlamydial bacteria of the Planctomycetes-Verrucomicrobia-Chlamydiae (PVC) superphylum are important pathogens of terrestrial and marine vertebrates, yet many features of their pathogenesis and host specificity are still unknown. This is particularly true for families such as the Waddliacea which, in addition to epithelia, cellular targets for nearly all Chlamydia, can infect and replicate in macrophages, an important arm of the innate immune system or in their free-living amoebal counterparts. An ideal pathogen model system should include both host and pathogen, which led us to develop the first larval zebrafish model for chlamydial infections with Waddlia chondrophila. By varying the means and sites of application, epithelial cells of the swimbladder, endothelial cells of the vasculature and phagocytosing cells of the innate immune system became preferred targets for infection in zebrafish larvae. Through the use of transgenic zebrafish, we could observe recruitment of neutrophils to the infection site and demonstrate for the first time that W. chondrophila is taken up and replicates in these phagocytic cells and not only in macrophages. Furthermore, we present evidence that myeloid differentiation factor 88 (MyD88) mediated signalling plays a role in the innate immune reaction to W. chondrophila, eventually by Toll-like receptor (TLRs) recognition. Infected larvae with depleted levels of MyD88 showed a higher infection load and a lower survival rate compared to control fish. This work presents a new and potentially powerful non-mammalian experimental model to study the pathology of chlamydial virulence in vivo and opens up new possibilities for investigation of other members of the PVC superphylum.